2018
DOI: 10.3892/ijo.2018.4508
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of HOXA3 in lung adenocarcinoma and its relevant molecular mechanism analysed by RT-qPCR, TCGA and in silico analysis

Abstract: Recent studies have indicated that homeobox A3 (HOXA3) functions as a carcinogen in colon cancer and the methylation level of HOXA3 is significantly increased in lung adenocarcinoma (LUAD) tissues. However, at least to the best of our knowledge, few studies to date have been performed on HOXA3 in non-small cell lung cancer (NSCLC). Therefore, further studies on HOXA3 expression in NSCLC and the potential regulatory mechanisms are urgently required. In this study, HOXA3 expression in 55 tissues of cases of NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…For HOXA3, differential methylation profiles were found in glioma, lung and penile carcinomas, leading to its consideration as part of the methylome signature associated with these diseases [72,80,84,106].…”
Section: Hoxa Genes Methylated In Cancermentioning
confidence: 99%
“…For HOXA3, differential methylation profiles were found in glioma, lung and penile carcinomas, leading to its consideration as part of the methylome signature associated with these diseases [72,80,84,106].…”
Section: Hoxa Genes Methylated In Cancermentioning
confidence: 99%
“…This result also suggested the feasibility of our present results. While other genes have not been reported to be associated with COAD/READ/CRC, their associations with other cancers have also been reported, such as APBB1, HHIP, and HOXA3 with lung cancer [30][31][32][33];TCF7L1, HOXB3, and ABCC2 with pancreatic cancer [34][35][36][37]; SALL1 with neck cancer [38,39];C2CD4A with breast cancer [40]. These results suggest both their relevance and their role as prognostic genes for corresponding cancers.Based on the results of our study and the relationship between those genes and other kind of cancers found in previous studies, it is suggested that those genes mentioned above may be used as prognostic genes for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The co-expressed genes of SAC3D1 were obtained from the Multi Experiment Matrix (https://biit.cs.ut.ee/mem/index. cgi) (19) and COXPRESdb (http://coxpresdb.jp) (20). In the Multi Experiment Matrix, P<0.05 was regarded as statistically significant.…”
Section: Methodsmentioning
confidence: 99%